Tectono-magmatic evolution of the Weinsberg Composite Pluton (Bohemian Massif): AMS constraints on incremental emplacement during late-Variscan stress transition - Tadeáš Hájek; Kryštof Verner; David Buriánek; Friedrich Finger; Jan Valenta; Leta Megerssa; David Schiller (Journal of Structural Geology, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

How is international CCS discussed locally? The case of Iceland - Juanita von Rothkirch; Bjarnhéðinn Guðlaugsson; David Christian Finger; Michael Stauffacher (Global Environmental Change, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

The number of conspecific alarm substance donors notably influences the behavioural responses of zebrafish subjected to a traumatic stress procedure - Cailin van Staden; Karin Finger-Baier; David Weinshenker; Tarryn L. Botha; Linda Brand; De Wet Wolmarans (Fish Physiology and Biochemistry, 2025)
Zebrafish ( Danio rerio ) represents a complementary pre-clinical model in stress and anxiety research. Conspecific alarm substance (CAS), an alarm pheromone secreted by injured fish, acts as a warning signal and modulates fear responses. Given their schooling nature and that injury precedes CAS release, varying fresh CAS concentrations extracted from different numbers of CAS-donating zebrafish may uniquely influence trauma-related behaviours. Thus, we investigated the behaviour of juvenile and adult zebrafish exposed to traumatic stress protocols, in the presence of CAS extracted from varying numbers of donating zebrafish. Juveniles were assessed for anxiety and boldness in the light–dark and open field tests (LDT and OFT), while adults were assessed in the novel tank test (NTT) and novel OFT (nOFT). We found that (1) trauma minimally impacted juvenile behaviour regardless of donor-derived CAS concentrations, (2) trauma-exposed adults displayed reduced exploration and heightened risk-taking behaviours in the NTT and nOFT compared to control-exposed fish, (3) NTT and nOFT freezing behaviours were distinctly emulated in adult fish and (4) post-trauma behaviour in adults was influenced by the number of donors. Therefore, CAS concentration as determined by donor number has age-related effects on anxiety- and risk-taking behaviours in trauma-exposed zebrafish, a valuable finding for studies utilising fresh CAS as a stress trigger. While we did not directly investigate CAS concentration through serial dilution, our data are of significant translational and ethological relevance, highlighting the importance of in-house method standardization in stress-related studies utilizing fresh CAS as an alarm cue.

Current state of plant conservation translocations across Europe: motivations, challenges and outcomes - Sandrine Godefroid; Sam Lacquaye; Andreas Ensslin; Sarah Dalrymple; Thomas Abeli; Hannah Branwood; Inmaculada Ferrando Pardo; P. Pablo Ferrer Gallego; Elke Zippel; Luísa Gouveia; Carlos Alberto Lobo; Francisco Fernandes; et al. (Biodiversity and Conservation, 2025)

Riparian Soil Heavy Metal Contamination and Pollution Assessment and Management Planning Integrating Multiple Indices, Statistical and Geospatial Approaches - Aditi Majumdar; Kirti Avishek; David Christian Finger (Environmental Management, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Seasonal drought treatments impact plant and microbial uptake of nitrogen in a mixed shrub grassland on the Colorado Plateau - Rebecca Finger‐Higgens; David L. Hoover; Anna C. Knight; Savannah L. Wilson; Tara B. B. Bishop; Robin Reibold; Sasha C. Reed; Michael C. Duniway (Ecology, 2024)
For many drylands, both long‐ and short‐term drought conditions can accentuate landscape heterogeneity at both temporal (e.g., role of seasonal patterns) and spatial (e.g., patchy plant cover) scales. Furthermore, short‐term drought conditions occurring over one season can exacerbate long‐term, multidecadal droughts or aridification, by limiting soil water recharge, decreasing plant growth, and altering biogeochemical cycles. Here, we examine how experimentally altered seasonal precipitation regimes in a mixed shrub grassland on the Colorado Plateau impact soil moisture, vegetation, and carbon and nitrogen cycling. The experiment was conducted from 2015 to 2019, during a regional multidecadal drought event, and consisted of three precipitation treatments, which were implemented with removable drought shelters intercepting ~66% of incoming precipitation including: control (ambient precipitation conditions, no shelter), warm season drought (sheltered April–October), and cool season drought (sheltered November–March). To track changes in vegetation, we measured biomass of the dominant shrub, Ephedra viridis , and estimated perennial plant and ground cover in the spring and the fall. Soil moisture dynamics suggested that warm season experimental drought had longer and more consistent drought legacy effects (occurring two out of the four drought cycles) than either cool season drought or ambient conditions, even during the driest years. We also found that E. viridis biomass remained consistent across treatments, while bunchgrass cover declined by 25% by 2019 across all treatments, with the earliest declines noticeable in the warm season drought plots. Extractable dissolved inorganic nitrogen and microbial biomass nitrogen concentrations appeared sensitive to seasonal drought conditions, with dissolved inorganic nitrogen increasing and microbial biomass nitrogen decreasing with reduced soil volumetric water content. Carbon stocks were not sensitive to drought but were greater under E. viridis patches. Additionally, we found that under E. viridis , there was a negative relationship between dissolved inorganic nitrogen and microbial biomass nitrogen, suggesting that drought‐induced increases in dissolved inorganic nitrogen may be due to declines in nitrogen uptake from microbes and plants alike. This work suggests that perennial grass plant–soil feedbacks are more vulnerable to both short‐term (seasonal) and long‐term (multiyear) drought events than shrubs, which can impact the future trajectory of dryland mixed shrub grassland ecosystems as drought frequency and intensity will likely continue to increase with ongoing climate change.

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Resetting the uraninite geochronometer metasomatically: The role of Na-Ca-F-OH-bearing fluids at 450 and 600 °C and 200 MPa - Daniel E. Harlov; Michael Waitzinger; David Schiller; Fritz Finger (Chemical Geology, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Culture and agricultural biodiversity conservation - Yanbing Wang; Sergei Schaub; David Wuepper; Robert Finger (Food Policy, 2023)

Ecosystem resilience to invasion and drought: Insights after 24 years in a rare never‐grazed grassland - Michael C. Duniway; Rebecca Finger‐Higgens; Erika L. Geiger; David L. Hoover; Alix A. Pfennigwerth; Anna C. Knight; Matthew Van Scoyoc; Mark Miller; Jayne Belnap (Global Change Biology, 2023)
Understanding the resilience of ecosystems globally is hampered by the complex and interacting drivers of change characteristic of the Anthropocene. This is true for drylands of the western US, where widespread alteration of disturbance regimes and spread of invasive non‐native species occurred with westward expansion during the 1800s, including the introduction of domestic livestock and spread of Bromus tectorum , an invasive non‐native annual grass. In addition, this region has experienced a multi‐decadal drought not seen for at least 1200 years with potentially large and interacting impacts on native plant communities. Here, we present 24 years of twice‐annual plant cover monitoring (1997–2021) from a semiarid grassland never grazed by domestic livestock but subject to a patchy invasion of B. tectorum beginning in ~1994, compare our findings to surveys done in 1967, and examine potential climate drivers of plant community changes. We found a significant warming trend in the study area, with more than 75% of study year temperatures being warmer than average (1966–2021). We observed a native perennial grass community with high resilience to climate forcings with cover values like those in 1967. In invaded patches, B. tectorum cover was greatest in the early years of this study (1997–2001; ~20%–40%) but was subsequently constrained by climate and subtle variation in soils, with limited evidence of long‐term impacts to native vegetation, contradicting earlier studies. Our ability to predict year‐to‐year variation in functional group and species cover with climate metrics varied, with a 12‐month integrated index and fall and winter patterns appearing most important. However, declines to near zero live cover in recent years in response to regional drought intensification leave questions regarding the resiliency of intact grasslands to ongoing aridification and whether the vegetation observations reported here may be a leading indicator of impending change in this protected ecosystem.

Agricultural systems and biodiversity: evidence from European borders and bird populations - Dennis Engist; Robert Finger; Peter Knaus; Jérôme Guélat; David Wuepper (Ecological Economics, 2023)

Droughting a megadrought: Ecological consequences of a decade of experimental drought atop aridification on the Colorado Plateau - Rebecca Finger‐Higgens; Tara B. B. Bishop; Jayne Belnap; Erika L. Geiger; Edmund E. Grote; David L. Hoover; Sasha C. Reed; Michael C. Duniway (Global Change Biology, 2023)
Global dryland vegetation communities will likely change as ongoing drought conditions shift regional climates towards a more arid future. Additional aridification of drylands can impact plant and ground cover, biogeochemical cycles, and plant–soil feedbacks, yet how and when these crucial ecosystem components will respond to drought intensification requires further investigation. Using a long‐term precipitation reduction experiment (35% reduction) conducted across the Colorado Plateau and spanning 10 years into a 20+ year regional megadrought, we explored how vegetation cover, soil conditions, and growing season nitrogen (N) availability are impacted by drying climate conditions. We observed large declines for all dominant plant functional types (C 3 and C 4 grasses and C 3 and C 4 shrubs) across measurement period, both in the drought treatment and control plots, likely due to ongoing regional megadrought conditions. In experimental drought plots, we observed less plant cover, less biological soil crust cover, warmer and drier soil conditions, and more soil resin‐extractable N compared to the control plots. Observed increases in soil N availability were best explained by a negative correlation with plant cover regardless of treatment, suggesting that declines in vegetation N uptake may be driving increases in available soil N. However, in ecosystems experiencing long‐term aridification, increased N availability may ultimately result in N losses if soil moisture is consistently too dry to support plant and microbial N immobilization and ecosystem recovery. These results show dramatic, worrisome declines in plant cover with long‐term drought. Additionally, this study highlights that more plant cover losses are possible with further drought intensification and underscore that, in addition to large drought effects on aboveground communities, drying trends drive significant changes to critical soil resources such as N availability, all of which could have long‐term ecosystem impacts for drylands.

Marginal climate change abatement costs in Swiss dairy production considering farm heterogeneity and interaction effects - Robert Huber; Marta Tarruella; David Schäfer; Robert Finger (Agricultural Systems, 2023)

National leverage points to reduce global pesticide pollution - David Wuepper; Fiona H.M. Tang; Robert Finger (Global Environmental Change, 2023)

Tissue Distribution of Mercury in the Bodies of Wild American Alligators (Alligator mississippiensis) from a Coastal Marsh in Louisiana (USA) - Liberty A. Moore; John W. Finger; David L. Haskins; Ruth M. Elsey; Steven B. Castleberry; Travis C. Glenn; Charles H. Jagoe; I. Lehr Brisbin (Archives of Environmental Contamination and Toxicology, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Improved Value Generation from Residual Resources in Iceland: the First Step Towards a Circular Economy - David Christian Finger; Gudrun Saevarsdottir; Halldór Guðfinnur Svavarsson; Bryndís Björnsdóttir; Sigurjón Arason; Lea Böhme (Circular Economy and Sustainability, 2021)
Improved value generation and efficient use of resources are important steps national economies can implement to minimize the use of resources and mitigate the creation of waste and toxic emissions. The increase of resource efficiency is eminent to tackle the imminent challenges of depleting resources and the emerging environmental crisis. In this study, we explore the value generation and efficiency of resource recovery in waste streams in the most important economic sectors in Iceland, namely, (i) fisheries, (ii) domestic waste processing, (iii) geothermal energy production, and (iv) aluminium production. By describing the processes, the opportunities, and the market potential of the value generation through enhanced resource efficiency in the four case studies, we identify possible solutions towards a more sustainable society. The results reveal that the increase in resource efficiency reduces the environmental impacts, increases the economic output, and enhances the resilience of the economy. We conclude that the presented concepts of added value generation could be the first step towards a circular economy, adhering to a more sustainable world while preserving vital resources for the next generations. While our results are based on the presented examples in Iceland, the described processes of resource recovery can be applied in any other country with similar resources.

Do adults with non-communicable diseases meet the German physical activity recommendations? - Gorden Sudeck; Wolfgang Geidl; Karim Abu-Omar; Jonas David Finger; Inga Krauß; Klaus Pfeifer (German Journal of Exercise and Sport Research, 2021)
Introduction The numerous health benefits of physical activity (PA) for people with non-communicable diseases (NCDs) are well-documented. In Germany, there are limited data on whether adults with NCDs fulfill health-oriented PA recommendations. This study describes the prevalence of meeting PA recommendations among adults with select NCDs. Method Based on the national representative GEDA-2014/2015-EHIS ( N = 24,016), the self-reported PA data of the European Health Interview Survey–Physical Activity Questionnaire (EHIS-PAQ) were classified with respect to fulfilling recommendations for health-enhancing aerobic activities (≥ 150 min per week with at least moderate intensity) and muscle strengthening (≥ 2 times per week). These binary indicators were used to analyze the association between the prevalence of sufficient PA and the self-reported presence of certain NCDs and multiple NCDs to reflect multimorbidity. Results Compared to the general adult population, sufficient aerobic PA was lower for most NCDs, with the lowest level among people with diabetes mellitus, obesity, stroke, chronic obstructive pulmonary disease (COPD), and depression. Compared to the general adult population, sufficient muscle strengthening was lower for some NCDs (diabetes mellitus, obesity, depression), but it was higher in people with musculoskeletal diseases (osteoarthritis, lower back pain). Multimorbidity was negatively associated with sufficient PA levels. Conclusion The study specifies the need to promote PA among adults with select NCDs to counteract insufficient levels of health-enhancing PA and to reduce the individual and societal burden of NCDs.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Germany’s 2018 report card on physical activity for children and youth - Yolanda Demetriou; Jens Bucksch; Antje Hebestreit; Annegret Schlund; Claudia Niessner; Steffen C. E. Schmidt; Jonas David Finger; Michael Mutz; Klaus Völker; Lutz Vogt; Alexander Woll; Anne K. Reimers (German Journal of Exercise and Sport Research, 2019)

Application of Ti-in-zircon thermometry to granite studies: problems and possible solutions - David Schiller; Fritz Finger (Contributions to Mineralogy and Petrology, 2019)

Effects of selenium exposure on the hematology, innate immunity, and metabolic rate of yellow-bellied sliders (Trachemys scripta scripta) - David L. Haskins; Matthew T. Hamilton; Nicole I. Stacy; John W. Finger; Tracey D. Tuberville (Ecotoxicology, 2017)

Panta Rhei 2013–2015: global perspectives on hydrology, society and change - Hilary McMillan; Alberto Montanari; Christophe Cudennec; Hubert Savenije; Heidi Kreibich; Tobias Krueger; Junguo Liu; Alfonso Mejia; Anne Van Loon; Hafzullah Aksoy; Giuliano Di Baldassarre; Yan Huang; et al. (Hydrological Sciences Journal, 2016)

Lead contents of S-type granites and their petrogenetic significance - Fritz Finger; David Schiller (Contributions to Mineralogy and Petrology, 2012)

Effects of upstream hydropower operation and oligotrophication on the light regime of a turbid peri-alpine lake - Lorenz Jaun; David Finger; Markus Zeh; Michael Schurter; Alfred Wüest (Aquatic Sciences, 2007)

Effects of Alpine hydropower dams on particle transport and lacustrine sedimentation - Flavio S. Anselmetti; Raphael Bühler; David Finger; Stéphanie Girardclos; Andy Lancini; Christian Rellstab; Mike Sturm (Aquatic Sciences, 2007)

Effects of alpine hydropower operations on primary production in a downstream lake - David Finger; Peter Bossard; Martin Schmid; Lorenz Jaun; Beat Müller; Daniel Steiner; Erwin Schäffer; Markus Zeh; Alfred Wüest (Aquatic Sciences, 2007)

Present and past bio-available phosphorus budget in the ultra-oligotrophic Lake Brienz - Beat Müller; David Finger; Michael Sturm; Volker Prasuhn; Thomas Haltmeier; Peter Bossard; Catherine Hoyle; Alfred Wüest (Aquatic Sciences, 2007)

Impaired recognition of fear facial expressions in 5-HTTLPR S-polymorphism carriers following tryptophan depletion - Abigail A. Marsh; Elizabeth C. Finger; Beata Buzas; Niveen Soliman; Rebecca A. Richell; Meena Vythilingham; Daniel S. Pine; David Goldman; R. J. R. Blair (Psychopharmacology, 2006)

Low Levels of Nucleotide Diversity in Crocodylus moreletii and Evidence of Hybridization with C. acutus - David A. Ray; Jennifer A. Dever; Steven G. Platt; Thomas R. Rainwater; Adam G. Finger; Scott T. McMurry; Mark A. Batzer; Brady Barr; Peter J. Stafford; Jenna McKnight; Llewellyn D. Densmore (Conservation Genetics, 2004)

Deep‐water renewal in Lake Issyk‐Kul driven by differential cooling - Frank Peeters; David Finger; Markus Hofer; Matthias Brennwald; David M. Livingstone; Rolf Kipfer (Limnology and Oceanography, 2003)
During two field campaigns on Lake Issyk‐Kul in March and August 2001, 179 high‐resolution conductivity‐temperature‐depth profiles were measured, along with profiles of dissolved oxygen and light transmission. On the basis of this extensive data set, we investigated the large‐scale vertical advective processes responsible for deepwater renewal in Lake Issyk‐Kul. At some locations sampled in March, variable peak structures in the tracer profiles were observed that indicate horizontally localized intrusions. These intrusions have their origin in density plumesthat propagate along the bottom of the channels in the eastern shelf region. The cold dense water at the bottom of the channels is most likely generated by differential cooling of the water in the shallow shelf regions during winter. During summer, vertical advective processes appear to be limited to the upper 200 m, where upwelling in the open water leads to a doming structure. The August data support the results of earlier investigations that suggested that dynamic forcing by a basinwide gyre is responsible for the upwelling in the open water.